PENGARUH DISIPLIN KERJA TERHADAP KINERJA KARYAWAN HOTEL HARRIS RIVERVIEW KUTA - Permana, Kadek Bagus Jaya; Sihombing, Irene Hanna H.; Diwyarthi, Ni Desak Made Santi (JURNAL BISNIS HOSPITALITI, 2023)
Good human resource performance with a high work ethic will be able to help companies meet the company's targets and help the company gain profits, whereas if employee performance decreases and is bad it will harm the company. The purpose of this study was to determine whether or not there was an influence of work discipline on employee performance at the Harris Riverview Kuta Hotel. This study uses a quantitative approach . The subjects of this study were employees at the Harris Review Kuta Bali Hotel. The number of employees is 45 employees. the sample in this study were all employees, totaling 45 people. The analysis technique used is simple linear regression analysis. Based on the results of data analysis and discussion in the previous chapter, it can be concluded that work discipline has a positive and significant effect on the performance of employees at the Harris Riverview Kuta Hotel. based on the results of a simple linear regression test performed with the regression equation Y = 20.634 + 0.634x. The influence given is also a significant influence based on the results of the t test, with a calculated t value of 4.214 and a significance value of 0.000. The influence contribution given by the Work Discipline variable on Employee Performance is classified as a weak influence that is equal to 29.2%.